Earth Construction Techniques: Innovation and Sustainability - Silva, Mayume Nakata Da; Rodrigues , Mara Regina Pagliuso (Technical and Scientific Journal Green Cities, 2025)
Objective – This study aims to analyze earth construction techniques, evaluating their performance in terms of sustainability and climate adaptation. Methodology – A theoretical review of the main techniques was conducted. Originality/Relevance – This study fills a gap in the literature by comparing earth construction methods, highlighting cost-effective and environmentally-friendly solutions for the construction industry. Results – The prototypes indicated that earth construction techniques are effective in low-cost environments, with good structural resistance and low environmental impact. Theoretical/Methodological Contributions – The research presents a new perspective on the use of earth construction techniques, validating them with practical data for contemporary application. Social and Environmental Contributions – These techniques offer a sustainable housing alternative, particularly for low-income communities, reducing the environmental impact of the construction industry.